Integrated Formal Methods 9th International Conference, IFM 2012, Pisa, Italy, June 18-21, 2012. Proceedings - Derrick, John.; Gnesi, Stefania; Latella, Diego; Treharne, Helen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 9th International Conference on Integrated Formal Methods, IFM 2012, held Pisa, Italy, in June 2012. The 20 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 59 submissions. The papers cover the spectrum of integrated formal methods, ranging from formal and semiformal notations, semantics, proof frameworks, refinement, verification, timed systems, as well as tools and case studies.
Keywords: Computer science; Software engineering; Computer software; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Mathematical Logic and Formal Languages; Programming Techniques; Algorithm Analysis and Problem Complexity